Competence Analysis of State Civil Apparatus (ASN) Social Services in Polewali Mandar District - Andi Nur Fiqhi Utami; Aco Nata Saputra; Citra N. Fariaty (Journal of Scientific Research, Education, and Technology (JSRET), 2022)
This study aims to determine competency variables based on Spencer's theory which reveals that there are five main competency characteristics that affect individuals, namely, knowledge, skills, self-concept/attitude, traits, and motives. motives). In this study, the competence seen was from the aspects of knowledge, skills, and attitudes of employees towards their work at the Office of the Social Service of Polewali Mandar Regency. This type of research is descriptive qualitative. Data collection techniques carried out are through interviews, observation, and documentation. The research data obtained were then processed using qualitative analysis, namely data reduction, data presentation and conclusion. The results showed that the competence of employees at the Social Service Office of Polewali Mandar Regency was sufficient. This can be seen based on the good results of the indicators of knowledge and skills. However, related to attitude indicators, there are differences in the level of satisfaction among employees with their work. This needs to be considered so that employees can maximize their performance as state civil servants.